Analysis Leading Sectors and Poverty Impact in “Golden Triangle” Agglomeration Area - Chodijah; Risqi (Jurnal Ekonomi, 2025)
This study analyzes the leading sectors and their impact on poverty levels in Bojonegoro Regency, Tuban Regency, and Lamongan Regency from 2013 to 2023. The methods used include Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift Share analysis, and panel data regression to measure the influence of base sectors on poverty levels. The results indicate that several economic sectors have significant comparative advantages and the potential to support regional economic growth. However, the gap between economic growth and poverty levels persists, suggesting that the development of base sectors has not yet fully contributed to poverty reduction. Therefore, this study recommends optimizing leading sectors through more inclusive development policies to improve community welfare.